2018
DOI: 10.1017/s1751731117003457
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters for stayability to consecutive calvings in Zebu cattle

Abstract: Longer-lived cows tend to be more profitable and the stayability trait is a selection criterion correlated to longevity. An alternative to the traditional approach to evaluate stayability is its definition based on consecutive calvings, whose main advantage is the more accurate evaluation of young bulls. However, no study using this alternative approach has been conducted for Zebu breeds. Therefore, the objective of this study was to compare linear random regression models to fit stayability to consecutive cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 16 publications
1
6
2
1
Order By: Relevance
“…STAY53 and STAY63 presented heritability estimates equal to 0.15. These estimates are greater than those reported by Silva et al (), who presented heritability estimates of STAY63 in Nellore cattle ranging from 0.03 to 0.07. In contrast, the results of the present study corroborate with Teixeira et al () and Bonamy et al () who reported heritability for STAY63 of 0.14 and 0.16, respectively.…”
Section: Resultscontrasting
confidence: 69%
See 2 more Smart Citations
“…STAY53 and STAY63 presented heritability estimates equal to 0.15. These estimates are greater than those reported by Silva et al (), who presented heritability estimates of STAY63 in Nellore cattle ranging from 0.03 to 0.07. In contrast, the results of the present study corroborate with Teixeira et al () and Bonamy et al () who reported heritability for STAY63 of 0.14 and 0.16, respectively.…”
Section: Resultscontrasting
confidence: 69%
“…These estimates are greater than those reported by Silva et al (2017), Thus, one can conclude that, although STAY63 allows the female to be successful with up to two reproductive failures, it is not directly associated with cows that present reproductive failures concentrated at the beginning of its reproductive life. This may be associated with traditional Brazilian beef cattle production systems, where cows that do not re-breed and heifers that do not become pregnant during the breeding season, are culled.…”
Section: Genetic Parameter Estimatesmentioning
confidence: 62%
See 1 more Smart Citation
“…Simulation showed random regression may be somewhat better than other approaches for predicting the percentage of sires' daughters that survive to a specific age (Jamrozik et al, 2008). Random regression of stayability to consecutive calvings has shown that stayability to the second calving is a good indicator of stayability to later calvings (Jamrozik et al, 2013;Silva et al, 2018), enabling earlier evaluation of sire EBV based on daughters' records than is possible with a single observation of stayability to an older age.…”
Section: Discussionmentioning
confidence: 99%
“…Com as superfícies obtidas, pode-se prever os valores das propriedades para qualquer mistura do intervalo considerado com base nas proporções dos seus componentes [9,10]. Esta metodologia tem encontrado aplicações importantes em várias áreas tecnológicas, tendo sido aplicada em tecnologia de argilas com grande sucesso [11][12][13][14][15]. Em todos os casos essa metodologia levou a uma maior eficiência e confiança nos resultados obtidos e simultaneamente possibilitou a otimização dos sistemas com um mínimo de experimentos.…”
Section: Introductionunclassified